Ketoacidosis without significantly hyperglycaemia - is it possible? - Budzyński, Michał; Pekar, Joanna; Skolarczyk, Justyna Magdalena; Tadla, Monika; Skórzyńska-Dziduszko, Katarzyna (Journal of Education, Health and Sport, 2017)
Introduction and aim of the study. Currently only minimal information is available regarding ketoacidosis without significant hyperglycemia. Some study describe that the sodium –glucose cotransporters (SGLT) may alter the normal balance between gluconeogenesis and ketogenesis.Aim of the study is to present the problem of the occurrence of ketoacidosis without hyperglycemia. Results. Phlorizen, the sodium –glucose cotransporters SGLT inhibitor was recognized to increase acetoacetate reabsorption and to induce hyperketonemia to an extent comparable to that seen with insulin deﬁciency. SGLT2 is expressed on the α -cells of the pancreatic islets, functioning in their glucose-sensing mechanism, so that earlier reports of SGLT2 inhibition-induced hyperglucagonemia. Episodes of diabetic ketoacidosis with SGLT2 inhibitors use were characterized by lower blood glucose levels. Drugs as ipragliflozin, dapagliflozin and tofogliflozin (SGLT inhibitors) may increase ketogenesis. Ipragliﬂozin increases lipolysis and both fatty acid oxidation and ketogenesis. In trials of tofogliﬂozin hyperketonemia and ketonuria were reported, with dose-related increases both in β-hydroxybutyrate and acetoacetate. Conclusions. Ketoacidosis may cause by phlorizen – SGLT inhibitor with slightly / moderately elevated levels of blood glucose.